The change in pediatric subject symptoms during the COVID-19 pandemic in China: an increase in cardiac consultation - Yaqi Tang; Shujing Ma; Gang Luo; Zhixian Ji; Shuiyan Zhao; Yue Cao; Silin Pan (BMC, 2022)
Abstract Background It is reported that the adverse impact of nonpharmaceutical interventions (NPIs) on the mental health of children and adolescents may lead to psychologically related disorders during the coronavirus disease 2019 (COVID-19) period. Subject symptoms such as chest pain, chest tightness, and palpitation may be related to increased stress and anxiety in children and adolescents. The present research aimed to determine the number of pediatric consults and etiology of subject symptoms during the COVID-19 pandemic period and compared it with the same timelines in 2019 and 2021 to discuss the impact of different periods on the organic disease onset of children with subject symptoms, especially in cardiac involvement. Methods Children who visited Qingdao Women and Children's Hospital, Qingdao University between January 23 to April 30, 2019 (pre-COVID-19 period), January 23 to April 30, 2020 (COVID-19 period), and January 23 to April 30, 2021 (post-COVID-19 period) presenting chest pain, chest tightness, and palpitation were recruited. Information to determine gender, age, medical history, department for the initial visit, clinical manifestations, time from the latest onset to the visit, and diagnosis were recorded. Result A total of 891 patients were enrolled in the present study (514 males; median age: 7.72). One hundred twenty-three patients presented during the pre-COVID-19 period while 130 during the COVID-19 period, nevertheless, the number substantially increased during the post-COVID-19 period (n = 638). Cardiac etiology accounted for 1.68% (n = 15) of the patient population, including arrhythmias (n = 10, 1.12%), myocarditis (n = 4, 0.44%), and atrial septal defect (n = 1, 0.11%). There was no significant difference among groups in the distribution of organic etiology. The median time from the latest onset to the visit during the pre-COVID-19 period was 7 days compared to 10 days during the COVID-19 period and 3 days during the post-COVID period. Conclusion During the post-COVID-19 period, the median time from the latest onset to the visit was significantly shorter than that in the pre-COVID-19 period or COVID-19 period. The pediatric consult of children with subject symptoms presented increased substantially during the post-COVID-19 period, while there was no significant difference in the number of patients involving the cardiac disease. Clinicians ought to be more careful to screen heart diseases to prevent missed diagnosis and misdiagnosis during special periods.